Multi-dimensional service improvement under the multi-customer nature of container terminals - Huang, Sheng Teng; Bulut, Emrah; Duru, Okan (INDERSCIENCE ENTERPRISES LTD, 2016)
This paper investigates the complex environment of container terminal management under the multi-customer problem through the case of East Asian Terminals. Container terminals are service providers to cargo owners (i.e., shippers) as well as liner shipping firms (i.e., carriers) while priorities and requirements may differ. Terminal operators should define the equilibrium quality and configuration of terminal services subject to its own constraints (e.g., financial sustainability). The mainstream approach for evaluation of service quality needs to focus on a particular customer (or group of customers) ceteris paribus. In this paper, the multi-layer quality function deployment (ML-QFD) method is applied to the terminal operators in two-customer context (shippers and carriers). ML-QFD is capable of merging diversified perspectives of several customers and delivering an equilibrium outcome which may satisfy both stakeholders in a cooperative approach. Rather than indefinite superficial recommendations, ML-QFD gets to the point and finds specific technical measures which improve the intended problem. Empirical results (East Asian sample) indicate that both shippers and carriers fundamentally demand cheaper services while shippers also require rapid terminal operations in common with the literature. For achieving requirements of shippers and carriers (in equilibrium), the role of human resource management, operational excellence and automation are emphasised by subjects.
Keywords: container terminals; terminal management; multi-dimensional quality assessment; customer relationship management; CRM; FUNCTION DEPLOYMENT QFD; CONSISTENCY INDEX; PORT PERFORMANCE; QUALITY; PRIORITIES; SATISFACTION; CAPACITY; MODEL; Business & Economics; Transportation